2003
DOI: 10.1016/s0092-8674(03)00570-1
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanism of Cyclin D1 Action Encoded in the Patterns of Gene Expression in Human Cancer

Abstract: Here we describe how patterns of gene expression in human tumors have been deconvoluted to reveal a mechanism of action for the cyclin D1 oncogene. Computational analysis of the expression patterns of thousands of genes across hundreds of tumor specimens suggested that a transcription factor, C/EBPbeta/Nf-Il6, participates in the consequences of cyclin D1 overexpression. Functional analyses confirmed the involvement of C/EBPbeta in the regulation of genes affected by cyclin D1 and established this protein as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
320
2
6

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 386 publications
(333 citation statements)
references
References 39 publications
5
320
2
6
Order By: Relevance
“…Evidence for CDK-independent functions was first observed in clinical samples, wherein breast cancers overexpressing cyclin D1 failed to show enhanced proliferation rates, and control of the RB pathway was retained (Oyama et al, 1998;Lamb et al, 2003). In addition, B-cell lymphomas overexpressing cyclin D1 retained RB in its activated state (Zukerberg et al, 1996).…”
Section: Cell Cyclementioning
confidence: 99%
See 2 more Smart Citations
“…Evidence for CDK-independent functions was first observed in clinical samples, wherein breast cancers overexpressing cyclin D1 failed to show enhanced proliferation rates, and control of the RB pathway was retained (Oyama et al, 1998;Lamb et al, 2003). In addition, B-cell lymphomas overexpressing cyclin D1 retained RB in its activated state (Zukerberg et al, 1996).…”
Section: Cell Cyclementioning
confidence: 99%
“…Subsequent studies strikingly demonstrated that cyclin D1 is a modifier of gene transcription, and that this function of cyclin D1 has important implications in tumor biology. Specifically, cyclin D1 has been shown to regulate a number of sequence-specific transcription factors, including C/EBPb (Lamb et al, 2003), STAT3 (Bienvenu et al, 2001), DMP1 (Inoue and Sherr, 1998), and BETA2/NeuroD (Ratineau et al, 2002). The largest class of transcription factors regulated by cyclin D1 belong to the nuclear receptor superfamily, and include the estrogen receptor (Zwijsen et al, 1998;Lamb et al, 2000), androgen receptor (Knudsen et al, 1999;Reutens et al, 2001;Petre et al, 2002;Burd et al, 2005), thyroid hormone receptor (Pibiri et al, 2001), and peroxisome proliferator activated receptor-g (Qin et al, 2003).…”
Section: Cell Cyclementioning
confidence: 99%
See 1 more Smart Citation
“…Although preclinical and early clinical results have been encouraging, there is a real need for biomarkers for selecting those patients who may benefit most from anti-mTOR therapy (Morgensztern and McLeod, 2005;Johnston, 2006). Recent studies have defined mRNA expression patterns, or 'signatures', of deregulation of specific pathways -including Myc, Ras, cyclin D1, b-catenin, HER2/neu, epidermal growth factor receptor and mitogen-activated protein kinasein human cancer (Lamb et al, 2003;Sweet-Cordero et al, 2005;Bild et al, 2006;Creighton et al, 2006a, b). Preclinical studies indicate that these oncogenic signatures could be used as a guide for targeted therapies (Bild et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…C/EBPb is highly expressed in colorectal tumors (Rask et al, 2000) and is associated with ovarian tumor progression (Sundfeldt et al, 1999). Furthermore, C/EBPb can interact with cyclin D1 and appears to be important for the unique pattern of altered gene expression in human cancers that overexpress cyclin D1 (Lamb et al, 2003).…”
mentioning
confidence: 99%